Use of Air Photographs in Assessing Erosion in Upper Damodar Valley - Kumar Roy, Dilip; Bhattacharya, P.B. (Journal of Soil and Water Conservation, 2022)
The Upper Damodar Valley comprising an area of over 4.3 million acres extends over the Chotanagpur plateau in the eastern Indian States of Bihar and West Bengal. In the Valley two major dams each having a catchment area of over 1 million acres have been constructed at Maithon and Panchet and a third major dam having the same catchment area is under construction at Tenughat. In addition, two head-water dams have also been constructed at Konar and Tilaiya each having a catchment area of about 0.2 mi!lion acres. The region having landlorms belonging to Archaean and Gondwana groups presents an erosional land surface the physical, cultural and other aspects of which have been discussed at length by Gorric (1953). An intensive co-ordinated programme or soil and water conservation has been taken up in the area as a measure against premature siltation of the dams and to install proper physical protection to the watershed areas. A detailed and objective estimate of the erosion problems together with its areal distribution in the different areas of the Valley being essential at this stage of the soil conservation activities, attempts have been made in the present paper to assess the problems in relation to land use in the area, by interpretation of vertical air photographs taken in 1950.